The Role of Cognition and Affect in the Formation of Customer Satisfaction - A Dynamic Perspective - Homburg, Christian; Koschate, Nicole; Hoyer, Wayne D. (Journal of Marketing, 2006)
Despite the strong recognition that customer satisfaction should be viewed from a dynamic perspective, little is known about how the satisfaction judgment develops over time. Therefore, this study provides a dynamic analysis of the simultaneous influence of cognition and affect in the satisfaction formation process. The results of an experimental study based on a real consumption experience indicate that the impact of cognition on the satisfaction evaluation increases and the influence of affect decreases over time. Moreover, these effects are attenuated with inconsistent performance experiences. Finally, the study shows that the variance in customer satisfaction jointly explained by cognition and affect increases as experience accumulates. © 2006, American Marketing Association.
UnivIS-Import:2015-03-09:Pub.2006.rw.fbwiwi.migfk.therol